2008
DOI: 10.1111/j.1471-0528.2008.01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis by interviews and video recordings to establish the components of a skilled low‐cavity non‐rotational vacuum delivery

Abstract: Objectives The objectives of this study were to define the components of a skilled low-cavity non-rotational vacuum delivery (occiput anterior, vertex at station +2 or below and less than 45-degree rotation from midline) and to facilitate the transfer of skills from expert to trainee obstetricians.Design Qualitative study using interviews and video recordings.Setting Two university teaching hospitals (St Michael's Hospital, Bristol, and Ninewell's Hospital, Dundee).Participants Ten obstetricians and eight midw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Real-time video recording was used to provide a record of the procedure while creating the conditions of unsupervised HIVST [15]. Participants were instructed to perform the HIV self-test with the materials supplied.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time video recording was used to provide a record of the procedure while creating the conditions of unsupervised HIVST [15]. Participants were instructed to perform the HIV self-test with the materials supplied.…”
Section: Methodsmentioning
confidence: 99%
“…The need to manage the scenario on the simulator, as well as the need to run the simulator concurrent with evaluation, potentially confounds the evaluation process. Both video‐based evaluation and real‐time evaluation have been used successfully in an examinee‐centered approach, 2,11,12,18–21 but the two methods of evaluation have not been directly compared within the same scenario to determine reliability of assessment. We sought to determine the intermethod reliability of evaluation by real‐time versus videotape review.…”
mentioning
confidence: 99%
“…In such an approach, active engagement in the deliberate and repeated practice of particular tasks, immediate feedback, and time for problem-solving and evaluation have been shown to be more effective than the length of experience traditionally associated with achieving professional expertise. Other research has demonstrated the utility of videos in enabling practitioners to reflect on their own performance of complex clinical skills and clarify details which can be used to train others (Bahl et al, 2009). The use of videos as recommended by this panel may enable practitioners to develop complex pattern recognition associated with experience of real-life events, despite the paucity of actual VBBs available for most professionals to attend.…”
Section: Discussionmentioning
confidence: 98%